Demographic, epidemiological and clinical characteristics of Ukrainian war refugees with HIV infection in the Slovak Republic - Massmann, Ricardo; Doležalová, Kristína; Soják, Lubomír; Samsonová, Olena; Staneková, Danica Valkovičová; Zahornacký, Ondrej; Jarčuška, Pavol; Záriš Vachalíková, Mária; Vološinová, Diana; Piesecká, Ľubica; Vahalová, Veronika; Šimeková, Katarína; et al. (Travel medicine and infectious disease, 2024)
BACKGROUND: The Slovak Republic, an Eastern European country, borders Ukraine, which has one of the highest rates of HIV/AIDS in Europe. This study aims to inform readers about the demographic characteristics of Ukrainian war refugees with HIV/AIDS seeking temporary protection status in Slovakia due to the Russian invasion of February 24, 2022. It focuses on their epidemiology, immunological profiles, co-infections, and treatment. DESIGN: Multicenter, retrospective study between March 1, 2022, and March 31, 2023. METHODS: Data were collected from all Ukrainian patients with refugee status living with HIV or newly diagnosed, who presented to any of the five HIV/AIDS centers in Slovakia. Information was obtained through medical interviews, physical examinations, laboratory tests and medical reports from the Ukrainian Ministry of Health. RESULTS: From March 1, 2022, to March 31, 2023, 141 Ukrainian refugees were included, mostly women (56.7 %, n = 80), with a median age of 41 years. The median CD4+ count was 680 cells/mL; 69.2 % (n = 97) had a viral load below 40 copies/mL. On arrival, 87.8 % (n = 123) were on ART, 90.2 % (n = 111) on dolutegravir. Coinfections included hepatitis C (31 %, n = 41), hepatitis B (12.5 %, n = 17), and tuberculosis (11.3 %, n = 16). Three died from AIDS complications. CONCLUSION: The study provides a detailed overview of the epidemiological, demographic, immunological, co-infection, and treatment characteristics of Ukrainian PLWHA displaced by the war to the Slovak republic. With the conflict ongoing, it is necessary to be prepared for more refugees in the coming months.
Keywords: dospělí; Female; AIDS; virová nálož; počet CD4 lymfocytů; Adult; mladý dospělý; ženské pohlaví; HIV; Antiretroviral therapy; Ukrajina; HIV Infections; Coinfection; Slovakia; lidé; Ukraine; koinfekce; uprchlíci; HIV infekce; retrospektivní studie; Male; Viral Load; Young Adult; CD4 Lymphocyte Count; lidé středního věku; Refugees; Slovenská republika; mužské pohlaví; Retrospective Studies; Middle Aged; Humans